A Comparative Study On Genre, Format And Changing Trends - Senthil Kumar, B; Perumal, Ayem; Manoj Kumar, Col; Nivedhitha, D (International Journal of Computer Sciences and Engineering, 2025)
The main aim of the research is to analyze the content of various genres of films released in South India. Also, it aimed to study the elements of commercial cinema and other genres of cinema. In this research, a case study was conducted to identify the impacts of various factors such as star value, characterisation and other elements like story, script, cinematography, music, editing, and visual effects. The South Indian film industry is very well developed in terms of film making methods, genres and visual effects. In this research, this development in films related to genres and different making methods is gathered and compared to study the current trends. The films which are being analyzed in this case study are, and CHANDRA MUKI, THEERAN ADHIGARAM ONDRU and MERKKU THODARCHI MALAI. These film genres are categorised into various formats such as a hybrid of horror and comedy genres, semi non-fictional and realistic fictional film. These films and formats reflect the current cinematic trends, changing mindsets of the south Indian filmgoers and the current society. This case study research tries to compare the current cinematic trends, current filmmaking genres and the latest developments in South Indian cinema industry. From this research, it is observed that many south films have been released during the past ten years with different genres and with different storytelling methods. The star value of the film plays an important role in the success of the film, particularly in the south Indian film industry. At the same time, the filmgoers of south India also accepted the newcomers and directors and new genres.